Investigating Unassociated Fermi-LAT sources for the search of Gamma ray pulsars including Millisecond pulsars using semicoherent approch - Hrishikesh Chandana A.; Morselli Aldo; Belardinelli Daniele; Rodriguez Fernandez Gonzalo; D’Antonio Sabrina; Fafone Viviana (EPJ Web of Conferences)
The search for gamma-ray pulsars including millisecond pulsars (MSPs) among unassociated Fermi-Large Area Telescope (LAT) sources offers an opportunity to study these rapidly rotating, highly magnetized neutron stars. This work uses semi-coherent data analysis method adapted from gravitational wave (GW) searches to detect periodic signals indicative of pulsar activity. Identified candidates are to be submitted to the LIGO-VIRGO-KAGRA (LVK) collaboration for further analysis, linking electromagnetic and GW observations for potential multimessenger insights. This research expands the pulsar catalog, providing insights to the GeV excess issue and enhancing the detection prospects of GW from isolated pulsars.